Developing an Integrated System Design Model for from Flexibility of Industrialized Residential Timber Building - Jaganathan, Siva (2011)
This study examines the integration of timber industrialized building system (TIBS)during the design process of a building project. Currently in Malaysia, timber has been mainly used for non-structural purposes. The study finds the fragmented process of design, manufacturing and assembly physical building elements and components of the prefabrication processes limiting design flexibility, hence, the final industrialized building forms are limited. This form limitation is inhibiting the consideration of using industrialized building system (IBS) by architects during design of their building projects. The objectives of this study are understanding the IBS design involved and proposing an integrated system design for producing an IBS building. In order to address, the study conducted an ethnography research method on a residential house that was built using prefabricated timber framing system to document the various stages of a timber IBS lifecycle, such as the design, the manufacturing/production and the assembly processes. The study found the existence of multiple task interdependencies that required varied design decision-makings during the iterative design process. In addition to that it also found the lack of integration between the form finding categories such as functional space design,physical building elements and components design during the application of a system design in IBS building’s. The ethnography findings highlight the need for a systematic design process and approach of the physical building components that supports off-site manufacturing/production and assembly-able construction, which in turn would allow designing a flexible form for timber industrialized building system.The ethnography results then led to the development of an integrated system design model for industrialized building in timber and the development of the spacer architectonic building system that supports form flexibility of architectural design. The integrated system design model actually merges the design development and detailed design/construction documentation phases of the architectural design lifecycle thereby shortening the duration of the design phase while reducing redundant design flaws occurred during the manufacturing/production and assemblyable construction. These contributions are expected to enhance timber as a green building that supports sustainable development as per recommended by the Construction Industry Master Plan 2006-2015.